Pengaruh Motivasi, Lingkungan Kerja, dan Budaya Organisasi terhadap Kinerja Pegawai Melalui Kepuasan Kerja sebagai Variabel Mediasi (Kajian Studi Literatur Manajemen Sumber Daya Manusia) - C.H Dethan, Selvi; E. H. J. Foeh, John; A. Manafe, Henny (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Writing this article is also meant to be able to determine the hypothesis that has an impact on each variable so that it can be used for subsequent writing. The results of this study are 1) Motivation has a positive influence and is quite important for job satisfaction; 2) The work environment has a positive influence and is quite important for job satisfaction; 3) Organizational culture has a positive influence and is quite important for job satisfaction; 4) Motivation has a positive effect and is quite important for employee performance; 5) The work environment has a positive influence and is quite crucial for performance; 6) Organizational culture has a positive influence and is quite essential for employee performance. 7) Job satisfaction has a positive and significant influence on employee performance. 8) Job satisfaction mediates the influence of motivation, work environment, and organizational culture on employee performance.